The relationship between emotional intelligence and turnover intention among employees of Secure Parking Corporation Sendirian Berhad, Petaling Jaya, Selangor, Malaysia - Ong, Shi Keat, author; Muhammad Daud, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2011)
Project Paper (Sarjana Muda Psikologi(Industri dan Organisasi)) - Universiti Teknologi Malaysia, 2011